2014
DOI: 10.11648/j.cb.20140202.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium on the Liver and Amelioration by Aqueous Extracts of Fenugreek Seeds, Rosemary, and Cinnamon in Guinea pigs: Histological and Biochemical Study

Abstract: Hepatotoxic agents can react with the basic cellular components and consequently induce almost all types of liver lesions. Objective: The present work aimed to evaluate effectiveness of fenugreek seeds, rosemary and cinnamon against cadmium induced hepatotoxicity in guinea pigs from the histological and biochemical aspects. Materials and methods: 48 guinea pigs were used for this study and divided into 8 groups. The first 4 groups were control groups, the 5 th group was the experimental and administered oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
7
15
0
Order By: Relevance
“…These results are in agreement with Bolanle [2011] who reported that A significant increase (P<0.05) was observed in the activity of liver enzymes (AST, ALT, ALP) of hypercholesteremic rats when compared with normal control while a significant decrease (P<0.05) was observed when comparing the hypercholesterolemia rats with the group of rats treated with ginger powder at 5% and 10% level and a similar result was reported by Al-Naqeeb [2003] who reported that the administration of aqueous extract of ginger to rats, orally and intraperitoneally, at two different levels of doses, significantly decreased the activities of some serum enzymes such as (AST) and (ALT). Also, these results are in agreement with Albasha and Azab [2014] who reported that aqueous extract of rosemary has significantly decreased the release of AST. This may be due to the hypercholesterolemia diet could have caused deposition of fats in the hepatocytes which may lead to damage of the cells and hence leakage.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with Bolanle [2011] who reported that A significant increase (P<0.05) was observed in the activity of liver enzymes (AST, ALT, ALP) of hypercholesteremic rats when compared with normal control while a significant decrease (P<0.05) was observed when comparing the hypercholesterolemia rats with the group of rats treated with ginger powder at 5% and 10% level and a similar result was reported by Al-Naqeeb [2003] who reported that the administration of aqueous extract of ginger to rats, orally and intraperitoneally, at two different levels of doses, significantly decreased the activities of some serum enzymes such as (AST) and (ALT). Also, these results are in agreement with Albasha and Azab [2014] who reported that aqueous extract of rosemary has significantly decreased the release of AST. This may be due to the hypercholesterolemia diet could have caused deposition of fats in the hepatocytes which may lead to damage of the cells and hence leakage.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the activities of SOD, CAT, and GP X were decreased in the liver and kidney of Cd-treated rats. This comes in agreement with many reports [11,38]. SOD activity is strongly inhibited by Cd, probably by interacting with metal moieties of SOD (Cu, Zn, or Mn) and thus reducing activity.…”
Section: Lipid Peroxidation and Antioxidant Enzymessupporting
confidence: 93%
“…The exposure to Cd chloride significantly lowered the concentrations of total protein and albumin compared with concentration values obtained for the control group (Table 2). Similar observations were reported in many experimental investigations on animals exposed to Cd [11,24]. The increased levels of studied enzymes in Cd-induced rats indicate an increased permeability and damage and/or necrosis of hepatocytes [9], which increase the release of these enzymes in the bloodstream [25].…”
Section: Biochemical Indicators Of Liver Functionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the natural antioxidant system may not always be equal to the task [15]. Natural antioxidants strengthen the endogenous antioxidant defenses from reactive oxygen species and restore the optimal balance by neutralizing reactive species [16] [17] [18] [19]. The antioxidant activities of phenolics are related to a number of different mechanisms, such as free radical-scavenging, hydrogen-donation, singlet oxygen quenching, metal ion chelation, and acting as a substrate for radicals such as superoxide and hydroxyl [20].…”
Section: Introductionmentioning
confidence: 99%